Carbon footprint of open-cut pipelines (NZ context) : Massey University, New Zealand - Manalo, Kevin (Massey University, 2023)
Society is currently facing a climate crisis; our human activities, notably the burning of fossil fuels, emit greenhouse gases into the atmosphere. The constant addition of GHG emissions is resulting in climate change. Nearly all countries agreed in the Paris Agreement 2015 to limit the global temperature increase to well below 2°C above pre-industrial levels. Science-based projections depict a concerning future. Should there be a failure to adequately mitigate our emissions, the impacts on humans and other species could be catastrophic. The Construction Industry is a vital sector that significantly contributes to a nation’s economic and social development. It builds and maintains infrastructure and serves as a significant source of employment. Buildings and construction account for 39% of global emissions, with 36% attributed to global energy use. While most research focuses on emissions from construction buildings, a literature review shows a lack of information regarding global infrastructure emissions. Recent research by Thacker et al. (2021) addresses this gap; when they combine infrastructure, building and construction, the total global emission amounts to a significantly higher value of 79%. Focusing on the stormwater, water, and wastewater sectors (three waters), the emissions amount to 5% of all emissions. Although water/wastewater emissions are only 5% of the costs, adaptation costs in the water sector are estimated to account for 54% of all costs. In Aotearoa, New Zealand, government and local authorities are making progress in capturing and reducing their carbon emissions. For instance, Auckland Council has set their goal to reduce greenhouse gas emissions by 50% by 2030, and Watercare aims to reduce its construction emissions by 40% by 2025; this is only two years away. Should local authorities impose the need to start reporting on carbon emissions on the construction industry, especially those in asset infrastructure delivery, research from the existing literature shows that the construction industry is not ready, not equipped, sees little need to do things differently, or does not know how to quantify carbon emission. The gaps in the research show that contractors should begin their carbon journey, and there are multiple carbon frameworks or standards without explicit critique on what works best. Understanding and knowing these standards takes time, and without a clear lead, information on critical inputs and variables required to represent the construction works accurately becomes muddy. As the standards were written to cater to different industries, the steps given are generic and do not go into detail about specific construction activities. Existing literature cautions that if the method and level of detail are unclear, final carbon footprint values can change. Further, emission sources need to be measured and quantified. However, units of measurement for these activities and productivity durations are typically not published as knowledge of these productivities is a trade secret and a competitive advantage to construction activity. To add to the complexity, the carbon science or emission factors that correspond to the emission activities are not readily available, and more research is needed to find local emission factor sources. In response to these challenges, the research aims to create and develop a simplified methodology and a template for contractors to create their carbon inventory on installing three waters open-cut pipeline excavation. A new Carbon Framework Methodology was developed based on the literature findings and data collection to fulfil the aim. A case study scenario was created where a 100ø PVC pipe is installed, and a 1.3m deep open-cut trench is excavated using standards based on Auckland Council stormwater and Watercare water and wastewater standards. An Excel-based carbon tool was created, and the steps in the carbon framework were followed. The final calculated carbon footprint values were verified using published Environmental Product Declarations (EPD). The carbon tool was presented to 18 participants from 1 tier one and multiple tier 2 contractors who have been installing water, wastewater and stormwater pipelines, with some contractors having over 20+ years in the industry. The research found that creating a carbon inventory is complex, multi-disciplined, requires construction methodology knowledge, and cannot avoid the need to learn carbon principles and carbon science (emission factors). The findings are significant as they discuss the implications of Carbon Accounting for Contractors, from knowing operation boundaries (Scope 1, 2 and 3) to the cost of upskilling, embedding, and implementing carbon management in construction projects. Minor findings were also discussed on the implications of Carbon Accounting for Designers and the heavy responsibility for Clients in ensuring that the capture of carbon emissions flows downstream to its value chain.
Keywords: Construction Pipeline; Carbon Footprint; Carbon Framework; NZ; 400504 Construction engineering; 401102 Environmentally sustainable engineering